2018
DOI: 10.1155/2018/2635202
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Is Correlated with Widespread Diffusion Tensor Imaging (DTI) Impairment in Amyotrophic Lateral Sclerosis

Abstract: Apathy is recognized as the most common behavioral change in several neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), a multisystem neurodegenerative disorder. Particularly, apathy has been reported to be associated with poor ALS prognosis. However, the brain microstructural correlates of this behavioral symptom, reported as the most common in ALS, have not been completely elucidated. Using diffusion tensor imaging (DTI) and tract-based spatial statistics (TBSS), here we aimed to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 85 publications
(104 reference statements)
1
11
0
Order By: Relevance
“…The DLPFC-caudate circuits have been implicated as playing a key role in all forms of apathy (Pagonabarraga et al, 2015). Our study revealed that apathy severity was positively correlated with executive dysfunction, which is consistent with previous reports (Femiano et al, 2018;Brown et al, 2019). However, no correlation was observed between apathy severity and the ALFF in this region, after controlling for executive function, in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The DLPFC-caudate circuits have been implicated as playing a key role in all forms of apathy (Pagonabarraga et al, 2015). Our study revealed that apathy severity was positively correlated with executive dysfunction, which is consistent with previous reports (Femiano et al, 2018;Brown et al, 2019). However, no correlation was observed between apathy severity and the ALFF in this region, after controlling for executive function, in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…So far, no study has explored these abnormalities using the cerebellar peduncles. Previous studies have examined WM abnormalities in the whole cerebellum rather than cerebellar peduncles, corticospinal tract, corpus callosum and extra-motor brain regions ( Thivard et al, 2007 , Verstraete et al, 2010 , Canu et al, 2011 , Cirillo et al, 2012 , Trojsi et al, 2015 , Femiano et al, 2018 , Bede et al, 2015 ). Unlike other studies ( Tan et al, 2014 ), we did not find GM atrophy in any of the cerebellar lobules.…”
Section: Discussionmentioning
confidence: 99%
“…the precentral gyrus, parietal and occipital areas along with the subcortical areas such as the cerebellum ( Kassubek et al, 2005 , Agosta et al, 2007 , Agosta et al, 2012 , Thivard et al, 2007 , Verstraete et al, 2010 , Douaud et al, 2011 , Ferraro et al, 2017 , Menke et al, 2017 , Shen et al, 2018 ). Diffusion tensor imaging (DTI) studies have also reported altered diffusivity in the cerebellum, insula, corpus callosum, corticospinal tract and the frontal, temporal and occipital areas ( Agosta et al, 2007 , Thivard et al, 2007 , Verstraete et al, 2010 , Canu et al, 2011 , Douaud et al, 2011 , Bede et al, 2015 , Trojsi et al, 2015 , Femiano et al, 2018 ). Altogether, these findings across multiple different MRI measures suggest a consistent feature of structural and functional impairment of the cerebellum in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Most cross-sectional studies have shown no correlation between the severity of behavioral changes and time elapsed between disease onset and the time of study, suggesting that there is no significant decline over time (Woolley et al, 2011; Bock et al, 2017; Femiano et al, 2018). Crockford et al (2018) assessed behavior in a sample of 149 patients using the ECAS caregiver behavioral interview and examined whether behavior was related to disease stages according to King’s Clinical Staging System (stage 1 from stage 4 depending on the number of affected bodily regions).…”
Section: Cognitive Emotional and Behavioral Changes In Alsmentioning
confidence: 99%
“…Diffusion tensor imaging studies have shown a significant negative correlation between apathy scores and fractional anisotropy in the right anterior cingulate region, corpus callosum, bilateral amygdalae, left thalamus, and fornix, with atrophy of these brain regions (Woolley et al, 2011; Branco et al, 2018; Femiano et al, 2018). Correlations between apathy and the prefrontal cortex have also been found in other neurological diseases.…”
Section: Cognitive Emotional and Behavioral Changes In Alsmentioning
confidence: 99%